Traditional breeding objectives and practices of goat, sheep and cattle smallholders in The Gambia and implications in relation to the design of breeding interventions - Ejlertsen, M.; Poole, Elizabeth J.; Marshall, Karen (Springer, 2012)
This paper describes the traditional breeding objectives and practices of West African Dwarf goat, Djallonke sheep, and N'dama cattle keepers in The Gambia and discusses the implications of these on the design of breeding-related interventions to improve livestock productivity. Data were collected via surveys implemented within three study sites in The Gambia, where traditional mixed crop-livestock smallholder farming predominates. The surveys comprised a participatory rural appraisal conducted in nine communities and a household questionnaire targeting 238 households. Livestock-keeping households were classified as 'poorer' or 'wealthier' based on the number of cattle owned. The most important objectives for keeping all species of livestock for the poorer groups (0 to 10 cattle) was 'savings and insurance', followed by 'income' and 'ceremonial/dowry' for the small ruminants and 'manure' and 'draught' for both cows and bulls. In contrast, for the wealthier group (more than 10 cattle), savings and insurance was the fourth to seventh ranked production objective (depending on species), with the most important production objectives being ceremonial/dowry for goats, income for sheep and manure for cows and bulls. An analysis of breeding practices indicated that breeding animals are selected on criteria which partially align to the breeding objectives, animals are rarely purchased for the purpose of breed improvement, knowledge of the cause and consequence of inbreeding is low and breeding decision makers may not necessarily be the livestock owner, particularly if the livestock owner is a women. Given this, it is suggested that capacity building on breeding-related issues, particularly in relation to the selection of breeding animals and specifically targeted at the different socioeconomic groups of livestock keepers, may be an appropriate, effective and relatively low-cost breeding intervention.